2021
DOI: 10.1021/acsapm.1c00956
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Dwell Stage in the Cure Cycle on the Interphase Formation in a Poly(ether imide)/High Tg Epoxy System

Abstract: Epoxies are inherently brittle materials and to overcome this brittleness, a second microphase (i.e., thermoplastic) is typically added. This modification of epoxy resin using thermoplastics results in reaction-induced phase separating morphologies in the micrometer range. In this study, the influence of the curing history, beyond phase separation, on the interphase formation and final morphology of PEI and the high T g epoxy system is investigated. Several cure cycles were examined, each with a first dwell te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 34 publications
3
20
0
Order By: Relevance
“…The actual time for interphase formation is much less than 60 s, as the highest diffusion rate prevails in the beginning of the curing. As the chain mobility reduces with a higher degree of curing, the diffusion rate drops rapidly, eventually leading to the maximum interphase thickness within the first 10 s of curing [ 28 , 30 , 31 , 50 ]. Voleppe et al [ 51 ] showed that the penetration at the front of the thermoset continued beyond phase separation, whereby both mechanisms overlapped.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The actual time for interphase formation is much less than 60 s, as the highest diffusion rate prevails in the beginning of the curing. As the chain mobility reduces with a higher degree of curing, the diffusion rate drops rapidly, eventually leading to the maximum interphase thickness within the first 10 s of curing [ 28 , 30 , 31 , 50 ]. Voleppe et al [ 51 ] showed that the penetration at the front of the thermoset continued beyond phase separation, whereby both mechanisms overlapped.…”
Section: Resultsmentioning
confidence: 99%
“…The affinity between thermoset and thermoplastic is the crucial element for creating joints with high strength [ 13 , 26 , 27 , 28 ]. A gradient interphase forms between the reactive epoxy resin and the thermoplastic material, whereby the two components partially dissolve, diffuse, and, finally, decompose due to a reaction-induced phase separation [ 29 , 30 , 31 ]. The overall composition or cross-link density of the material varies from location to location at the macroscopic level [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…To measure the interphase formation and characterize its microstructural properties as a function of temperature, an optical hot-stage microscopy setup was used, as used by Teuwen and Farooq et al [ 9 , 12 , 24 ], where a controlled heating device (Linkam THMS600, Tadworth, Great Britain) was coupled with optical microscopy (Keyence VHX 600, Osaka, Japan). Figure 1 shows the adapted measurement stack.…”
Section: Methodsmentioning
confidence: 99%
“…The general concept proposes incorporating a second polymer in the epoxy matrix that is used as a toughening agent to prevent the crack propagation, thus leading to the improvement of the fracture toughness [ 5 ]. Several thermoplastics have been studied to toughen high-performance aerospace epoxy systems, such as poly(hydroxy ether) (phenoxy), poly(ether sulfone) (PES), poly(ether imide) (PEI) and poly(etherether ketone) (PEEK) [ 4 , 6 , 7 , 8 , 9 ]. The formation of interpenetrating polymer networks (IPN) and phase separating morphologies is an essential mechanism to improve fracture toughness [ 4 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation